An-Nadriyatu As-Sulukiyatu Wa Tatbiqu Tadriisi Al-Mufradati Al-Arabiyati - M. Fathor Rohman; Nurul Hanani; Isna Finurika (TADRIS AL-ARABIYAT: Jurnal Kajian Ilmu Pendidikan Bahasa Arab, 2023)
The theory of Behaviorism is one of the educational theories that is connected with theories in psychology, so a theory in learning psychology was born which seeks to relate learning to psychology, where this theory focuses on studying human behavior that is visible and can be felt by people who practice it. The method in this study used library research, which is a method of collecting data by understanding and studying theories from various literature related to this research. while Mufrodat or vocabulary is a tool for interpreting, as well as a means of thinking, with vocabulary, speakers can think and then translate their thoughts into words that convey what they want. In the application of Behaviorism Theory in learning Mufrodat there is an important role of a teacher in implementing vocabulary teaching appropriately to students after students are accustomed to it by the teacher, it is expected that students can apply it. So in this theory there is a vocabulary teaching strategy that can be used as to determine the method used by the teacher in teaching material according to the level of students.